Diffusion of XBRL Innovation Model of Adoption and Usage - Al-Rawashdeh, Awni Atallah (2011)
Motivated by the purported benefits of XBRL, yet its slow adoption by financial data consumers, the aims of this study are to determine the significant factors affecting the adoption and usage of XBRL amongst financial data consumers. However, currently no model addresses this problem from the viewpoint of financial data consumers, which is the focus of the proposed model. The model is developed by using technology diffusion and adoption theories such as Diffusion of Innovation (DOI), Theory of Reasoned Action (TRA), Theory of Planned Behavior (TPB), Decomposed Theory of Planned Behavior (DTPB), Campeau Social Cognitive Theory (CSCT), Technology Acceptance Model (TAM), Technology Acceptance Model 1999 (TAM1999), Technology Acceptance Model 2 (TAM2), Technology Acceptance Model 2001 (TAM2001), unified theory of acceptance and use of technology (UTAUT) and use diffusion model(UD). The data was collected using an online survey approach. The findings of this study indicate that attitudinal and control factors are significant factors in explaining financial data consumers' behavior intentions to adopt XBRL. In term of usage, HTML & PDF users are significantly different in 11 out of 23 online services. All these findings can be used by the regulators or industry to futher increase the adoption and usage of XBRL amongst financial data consumers.